2022
DOI: 10.1155/2022/2151840
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Blood Urea Nitrogen to Creatinine Ratio and the Prognosis of Critically Ill Patients with Cerebral Infarction: A Cohort Study

Abstract: Background. To evaluate the association between blood urea nitrogen (BUN) to creatinine (Cr) (BUN/Cr) ratio and the in-hospital mortality of critically ill patients with cerebral infarction in intensive care unit (ICU). Methods. In this cohort study, the data of 3059 participants with cerebral infarction were collected from the Medical Information Mart for Intensive Care (MIMIC)-III and the MIMIC-IV database. After propensity score matching (PSM) on age and gender, 2085 people were involved in and divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In another recent study involving 203 patients, the authors concluded that the BUN/Cr ratio is associated with larger volumes of ischemic tissue measured using diffusion-weighted imaging (DWI), and worse neurological deficits, as assessed by the NIHSS score, in AIS on admission ( 15 ). A broader exploration involving 3,059 AIS cases drawn from the Medical Information Mart for Intensive Care (MIMIC)-III and MIMIC-IV databases, with 2,085 cases subjected to propensity score matching (PSM) based on age and gender, indicated a slight association between the BUN/Cr ratio and an increased risk of in-hospital mortality in patients with AIS (RR = 1.01, 95% CI: 1.01, 1.02) ( 6 ). The disparities between these findings and those of the current study may be attributed to various factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another recent study involving 203 patients, the authors concluded that the BUN/Cr ratio is associated with larger volumes of ischemic tissue measured using diffusion-weighted imaging (DWI), and worse neurological deficits, as assessed by the NIHSS score, in AIS on admission ( 15 ). A broader exploration involving 3,059 AIS cases drawn from the Medical Information Mart for Intensive Care (MIMIC)-III and MIMIC-IV databases, with 2,085 cases subjected to propensity score matching (PSM) based on age and gender, indicated a slight association between the BUN/Cr ratio and an increased risk of in-hospital mortality in patients with AIS (RR = 1.01, 95% CI: 1.01, 1.02) ( 6 ). The disparities between these findings and those of the current study may be attributed to various factors.…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors affecting the prognosis of stroke, such as age, hypertension, diabetes, heart disease, and stroke etiology, which necessitate robust empirical substantiation. The intricate interplay between dehydration and poststroke prognosis remains a subject of sustained scholarly deliberation, with divergent perspectives on the correlation between dehydration and unfavorable outcomes (4)(5)(6), counterpoised by dissenting opinions (7)(8)(9). In addition, the previous studies were almost all linear studies, with either a small sample size or the insufficient collection of indicators.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we diligently improved our research methodology to ensure robust and accurate results. We used the MIMIC-III CareVue subset as an independent validation set, unlike previous studies that combined unfiltered data from MIMIC-III and MIMIC-IV (20)(21)(22)(23)(24), which can lead to data duplication and affect the stability and accuracy of results. In most research on ischemic stroke patients using the MIMIC database, the selection of cases is overly broad.…”
Section: Discussionmentioning
confidence: 99%
“…The BCR is a straightforward and readily obtainable measure, as it relies solely on venous blood samples in clinical settings. Previous studies have reported an association between the BCR and in-hospital mortality in various diseases (17)(18)(19)(20). BCR, a biomarker of neurohormonal activity, has been associated with poor prognosis in patients with acute heart failure and is an independent predictor of all-cause mortality (31).…”
Section: Discussionmentioning
confidence: 99%